Bullied, bystanders, and perpetrators in the workplace: The role of empathy in teachers and school leaders' experiences. Issue 3 (13th December 2021) - Mazzone, Angela; Pitsia, Vasiliki; Karakolidis, Anastasios; O'Higgins Norman, James
Abstract: This study investigated the experiences of workplace bullying among primary and postprimary school staff in Ireland. A sample of 630 teachers and members of the Senior Management Team (SMT) completed an online survey inquiring about their own experiences of bullying in the workplace, as targets, bystanders, and perpetrators. Information about respondents' perspective taking, empathic concern, personal distress, and demographic background was also collected. Results of the ordinal regression analysis showed a negative association of perspective taking with victimisation and bystander behaviour. In addition, respondents belonging to an SMT reported experiencing victimisation more frequently than teachers, while victimisation experiences and witnessing bullying were more common in postprimary than primary schools. Findings are discussed in terms of the importance of providing awareness and training programmes to school staff.